Specificity of Evidence Proceedings in Medical Trial - Selected Aspects - Kamieński, Grzegorz; Wiśniewska, Aleksandra; Borys, Adrian (Specyfika dowodzenia w procesie medycznym - wybrane aspekty, 2025)
The following publication presents the elements of evidence proceedings which are characteristic for so-called medical trials. The doctor’s involvement in civil proceedings, as an expert and a witness, was also analysed. The author discussed in detail the structure of a prima facie evidence. In this article the doctor’s involvement in civil proceedings was juxtaposed with a duty to maintain confidentiality of patient’s information.
Administracja publiczna i polityki publiczne. Tom poświęcony pamięci Profesora Ryszarda Herbuta, s. 154-166
Keywords: proceedings; medical expert; witness evidence; prima facie evidence; physician-patient privilege (doctor-patient confidentiality)